2003
DOI: 10.1016/s0194-5998(03)01590-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of amiodarone-induced thyrotoxicosis

Abstract: AIT can develop in any patient during or after amiodarone therapy. Medical management is extremely difficult due to the absence of a proven therapeutic armamentarium, and surgery offers a safe, viable option. Surgical management should play a larger role in treatment algorithms and should be strongly considered for patients whose conditions necessitate continuation of amiodarone, or with severe symptoms resistant to medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…However, this approach may be necessary in patients who are resistant to other treatments [65][66][67]. Recent studies have shown that total thyroidectomy can be performed in AIT patients without serious complications [68][69][70][71]. Pierret et al [72] performed 11 thyroidectomies in patients with AIT: 9 patients had no morbidity after elective surgery, while 2 patients required emergency surgery for multiple organ failure and cardiac problems.…”
Section: Total Thyroidectomymentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach may be necessary in patients who are resistant to other treatments [65][66][67]. Recent studies have shown that total thyroidectomy can be performed in AIT patients without serious complications [68][69][70][71]. Pierret et al [72] performed 11 thyroidectomies in patients with AIT: 9 patients had no morbidity after elective surgery, while 2 patients required emergency surgery for multiple organ failure and cardiac problems.…”
Section: Total Thyroidectomymentioning
confidence: 99%
“…Jednak postępowanie to może okazać się konieczne u pacjentów opornych na inne sposoby leczenia [65][66][67]. Ostatnie badania wykazały, że cał-kowite wycięcie tarczycy może być przeprowadzone u pacjentów z AIT bez poważnych powikłań [68][69][70][71]. Pierret i wsp.…”
Section: Typ 1 Aitunclassified
“…In contrast with type 2 AIT, definitive treatment of the underlying thyroid disease is generally needed after restoration of euthyroidism and removal of iodine load. This can be achieved with radioiodine therapy (usually after several months, because of persistent iodine contamination) or with total thyroidectomy, possibly after a short preparation with iopanoic acid 11–13 . However, it should be noted that iopanoic acid might not be easily available in other countries like the USA.…”
Section: Introductionmentioning
confidence: 99%
“…One would think whether this has implications for avoiding recurrent laryngeal nerve injury during thyroidectomy. According to some authors, a lower rate of this nerve injury could be attributable to conversation with the patient, being a type of monitoring . Nine patients (4 per cent) in the GA group and one patient (2 per cent) in the LA group had vocal cord palsy, but the difference was not statistically significant ( P = 0.512).…”
Section: Discussionmentioning
confidence: 94%